2018
DOI: 10.1038/mi.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroidales recruit IL-6-producing intraepithelial lymphocytes in the colon to promote barrier integrity

Abstract: Interactions between the microbiota and distal gut are important for the maintenance of a healthy intestinal barrier; dysbiosis of intestinal microbial communities has emerged as a likely contributor to diseases that arise at the level of the mucosa. Intraepithelial lymphocytes (IELs) are positioned within the epithelial barrier, and in the small intestine, function to maintain epithelial homeostasis. We hypothesized that colonic IELs promote epithelial barrier function through the expression of cytokines in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 46 publications
4
90
1
3
Order By: Relevance
“…A study by Kuhn et al provided more evidence for the crucial relationship between the microbiota, immune system, and intestinal epithelial barrier ( 71 ). Bacteria in the order Bacteroidales were sufficient to induce localization of intraepithelial lymphocytes in the colons of mice, and these cells were an important source of IL-6.…”
Section: Cytokine Actions On the Intestinal Epitheliummentioning
confidence: 99%
“…A study by Kuhn et al provided more evidence for the crucial relationship between the microbiota, immune system, and intestinal epithelial barrier ( 71 ). Bacteria in the order Bacteroidales were sufficient to induce localization of intraepithelial lymphocytes in the colons of mice, and these cells were an important source of IL-6.…”
Section: Cytokine Actions On the Intestinal Epitheliummentioning
confidence: 99%
“…In fact, many therapies under development aim to mobilize T-cell populations to seek and destroy tumor cells [ 109 ], a common goal of immunotherapies (discussed below in more detail). Another study by Kuhn et al demonstrated Bacteroidales to be important for intestinal membrane integrity by stimulating intraepithelial lymphocyte secretion of IL-6; however, while low levels of IL-6 are tolerable, increased levels of IL-6 promotes tumourigenesis by signaling proliferation, angiogenesis, and invasiveness while inhibiting apoptosis [ 110 , 111 ]. Cytokines such as IL-1β, TNF-α, and IL-6 are also produced by cells infected with viruses including Epstein-Barr Virus (EBV), HBV, HCV, and Kaposi’s sarcoma herpesvirus (KSHV), which induces an inflammatory environment and promotes tumourigenesis [ 112 , 113 , 114 ].…”
Section: Mechanism Of Action Of Microbes Associated With the Develmentioning
confidence: 99%
“…If a challenge induces the release of high levels of IFN-g, mimicked in this study by the i.p. injection of the cytokine, apical secretion of IL-6 will stimulate the activation of STAT3 in crypt surface epithelial cells to strength epithelial barrier functions (36,40). Lack of activation of STAT3 in IECs after i.p.…”
Section: Discussionmentioning
confidence: 99%
“…3D). However, the amount of Claudin-1, an epithelial protein induced by STAT3 (36) to strength barrier function in the gut, was strongly decreased in the colon in the absence of Crtam (Fig. 6E).…”
Section: Polarization and Compartmentalization Of The Il-6/stat3 Signmentioning
confidence: 99%